The Role of Human Platelet Preparation for Toll-Like Receptors 2 and 4 Related Platelet Responsiveness - Koessler, Juergen; Niklaus, Marius; Weber, Katja; Koessler, Angela; Kuhn, Sabine; Boeck, Markus; Kobsar, Anna (TH Open, 2019)
Background Like immune cells, platelets express the repertoire of toll-like receptors (TLR), among them TLR2 and TLR4, which are important for the recognition of bacterial patterns. Receptor-mediated functional effects in platelets have been investigated, but reliable conclusions are tampered due to heterogeneous study designs with variable platelet preparation methods. This study compares TLR2- and TLR4-dependent platelet responsiveness in platelet-rich plasma (PRP) and in washed platelets (WPs).Material and Methods Fresh peripheral blood samples from healthy donors served for the preparation of PRP and WP. Basal and agonist-stimulated TLR2 and TLR4 expression levels were evaluated by flow cytometry. Light transmission aggregometry was used to investigate functional effects of TLR2 and TLR4 stimulation with Pam3CSK4 or LPS (lipopolysaccharides from Escherichia coli) as ligands. The capacity of chemokine release was determined by immunoassays.Results Pam3CSK4 and LPS (in combination with thrombin) were able to induce aggregation in WP, but not in PRP, with threshold concentrations of 15 µg/mL. Basal expression levels of TLR2 and TLR4 were higher in WP than in PRP, increasing several-fold rapidly and persistently upon platelet activation with potent agonists. Pam3CSK4 (15 µg/mL) or LPS led to the submaximal release of RANTES, PF4, PDGF, NAP-2, and sCD40L from WP. In PRP, secretory effects are less pronounced for RANTES, PDGF, or PF4, and not detectable for NAP-2 or sCD40L.Conclusion The effects mediated by TLR2 and TLR4 stimulation are dependent on platelet preparation, an important issue for experimental designs and for manufacturing of platelet concentrates in transfusion medicine.
Keywords: toll-like receptor; lipopolysaccharides; chemokine; platelet preparation